2003
DOI: 10.1046/j.1365-2265.2003.01888.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the BclI polymorphism in the glucocorticoid receptor gene: association with sensitivity to glucocorticoids in vivo and body mass index

Abstract: We characterized a BclI-RFLP (restriction fragment length polymorphism) of the GR gene as a C/G polymorphism in intron 2 of which the G-allele was associated with hypersensitivity to glucocorticoids. This resulted in a lower BMI in older individuals in general, while our study in elderly males suggests that the lower BMI is probably due to a greater loss of lean mass during the ageing process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

22
251
7
6

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 295 publications
(286 citation statements)
references
References 20 publications
22
251
7
6
Order By: Relevance
“…Cortisol, MR, and GR SNPs in mental performance M Kuningas et al Previously, it has been shown that the GR gene polymorphisms alter HPA-axis responsiveness and thereby cortisol sensitivity. The ER22/23EK variation has been associated with resistance to cortisol (van Rossum et al, 2002), whereas the N363S and BclI polymorphisms were shown to increase the sensitivity to cortisol (Huizenga et al, 1998;van Rossum et al, 2002van Rossum et al, , 2003. We reasoned, that the increased resistance to cortisol attained by the ER22/23EK variant would protect against the damaging effects of highcortisol levels on cognitive decline and depression, whereas increased cortisol sensitivity would have opposite effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cortisol, MR, and GR SNPs in mental performance M Kuningas et al Previously, it has been shown that the GR gene polymorphisms alter HPA-axis responsiveness and thereby cortisol sensitivity. The ER22/23EK variation has been associated with resistance to cortisol (van Rossum et al, 2002), whereas the N363S and BclI polymorphisms were shown to increase the sensitivity to cortisol (Huizenga et al, 1998;van Rossum et al, 2002van Rossum et al, , 2003. We reasoned, that the increased resistance to cortisol attained by the ER22/23EK variant would protect against the damaging effects of highcortisol levels on cognitive decline and depression, whereas increased cortisol sensitivity would have opposite effects.…”
Section: Discussionmentioning
confidence: 99%
“…In the MR gene, the 215G/C and I180V single-nucleotide polymorphisms (SNPs) have been shown to change cortisol signaling in vitro (Arai et al, 2003), whereas in the GR gene the ER22/23EK, N363S, and BclI SNPs have been shown to change HPA-axis reactivity after a dexamethasone suppression test or a psychosocial stressor (Huizenga et al, 1998;van Rossum et al, 2002van Rossum et al, , 2003. In addition, the ER22/23EK variant has been associated with major depression in two studies (van Rossum et al, 2006;van West et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…BclI polymorphism has been associated with increased GC sensitivity determined by skin blanching response to topical GCs and increased cortisol suppression after low-dose DEX (19,38,39). In a large group of Dutch elderly individuals, subjects with the G allele had lower cortisol levels after dexamethasone suppression test as well as a tendency towards a decreased lean body mass and abdominal fat distribution, high blood pressure, altered insulin sensitivity, and cardiovascular risk factors, suggesting hypersensitivity to GC (38).…”
Section: Discussionmentioning
confidence: 99%
“…In a large group of Dutch elderly individuals, subjects with the G allele had lower cortisol levels after dexamethasone suppression test as well as a tendency towards a decreased lean body mass and abdominal fat distribution, high blood pressure, altered insulin sensitivity, and cardiovascular risk factors, suggesting hypersensitivity to GC (38). In 42 blood donors, association between the BclI variant genotype and an increased in vitro sensitivity to GCs was observed by DEX-mediated inhibition of concanavalin-A-stimulated PMBC (40).…”
Section: Discussionmentioning
confidence: 99%
“…; associated with cortisol levels (BclI) 34,35 ADRA2A Chromosome 10q25 ADRA2ADraI 6.3/6.3+6.3/6.7 (30%) 6.7/6.7 (70%) Unknown (DraI)…”
Section: Discussionmentioning
confidence: 99%